2011
DOI: 10.1523/jneurosci.1617-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Tsc1 In Vivo Impairs Hippocampal mGluR-LTD and Increases Excitatory Synaptic Function

Abstract: The autism-spectrum disorder Tuberous Sclerosis Complex (TSC) is caused by mutations in the Tsc1 or Tsc2 genes whose protein products form a heterodimeric complex that negatively regulates mTOR-dependent protein translation. Although several forms of synaptic plasticity, including metabotropic glutamate receptor-dependent long-term depression (mGluR-LTD), depend on protein translation at the time of induction, it is unknown if these forms of plasticity require signaling through the Tsc1/2 complex. To examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
178
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(203 citation statements)
references
References 46 publications
17
178
4
Order By: Relevance
“…A number of genetically based animal models of MCD have been developed, and most show robust hyperexcitability and/or spontaneous seizures (Wenzel et al, 2001;Kellinghaus et al 2004;Patel et al, 2004;Kwon et al, 2006;Harrington et al, 2007;Patrylo and Willingham, 2007;Nosten-Bertrand et al, 2008;Greenwood et al, 2009;Kerjan et al, 2009). When synaptic mechanisms have been investigated, these studies have typically reported postsynaptic alterations in glutamatergic excitatory Auerbach et al, 2011;Bateup et al, 2011;Luikart et al, 2011) or GABAergic inhibitory currents (Trotter et al, 2006;Ackman et al, 2009). For example, experimental tuberous sclerosis (TSC), caused by inactivating mutations in the TSC1 gene in vivo, is associated with greater postsynaptic AMPA and NMDA receptor-mediated currents, impaired long-term depression, and increased EPSC frequencies in the absence of altered presynaptic release probability (Auerbach et al, 2011;Bateup et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of genetically based animal models of MCD have been developed, and most show robust hyperexcitability and/or spontaneous seizures (Wenzel et al, 2001;Kellinghaus et al 2004;Patel et al, 2004;Kwon et al, 2006;Harrington et al, 2007;Patrylo and Willingham, 2007;Nosten-Bertrand et al, 2008;Greenwood et al, 2009;Kerjan et al, 2009). When synaptic mechanisms have been investigated, these studies have typically reported postsynaptic alterations in glutamatergic excitatory Auerbach et al, 2011;Bateup et al, 2011;Luikart et al, 2011) or GABAergic inhibitory currents (Trotter et al, 2006;Ackman et al, 2009). For example, experimental tuberous sclerosis (TSC), caused by inactivating mutations in the TSC1 gene in vivo, is associated with greater postsynaptic AMPA and NMDA receptor-mediated currents, impaired long-term depression, and increased EPSC frequencies in the absence of altered presynaptic release probability (Auerbach et al, 2011;Bateup et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…When synaptic mechanisms have been investigated, these studies have typically reported postsynaptic alterations in glutamatergic excitatory Auerbach et al, 2011;Bateup et al, 2011;Luikart et al, 2011) or GABAergic inhibitory currents (Trotter et al, 2006;Ackman et al, 2009). For example, experimental tuberous sclerosis (TSC), caused by inactivating mutations in the TSC1 gene in vivo, is associated with greater postsynaptic AMPA and NMDA receptor-mediated currents, impaired long-term depression, and increased EPSC frequencies in the absence of altered presynaptic release probability (Auerbach et al, 2011;Bateup et al, 2011). In contrast, our results suggest that enhanced excitatory synaptic drive in LIS1 mutants is attributable to enhanced neurotransmitter release.…”
Section: Discussionmentioning
confidence: 99%
“…Functional mutations in Tsc1 or Tsc2 significantly alter synapse structure, function, and plasticity (Tavazoie et al 2005;Ehninger et al 2008;Auerbach et al 2011;Bateup et al 2011;Chevere-Torres et al 2012). Protein synthesis, regulated by TSC-mTOR signaling, plays a role in learning-associated synaptic changes.…”
Section: Genetics Of Epilepsy and Autismmentioning
confidence: 99%
“…To address this issue, Bateup et al (2011) knocked out Tsc1 selectively in CA1 pyramidal neurons in P14 -16 mouse pups. The loss of Tsc1 produced hyperexcitable pyramidal cells caused by deficits in inhibitory synaptic function manifested as decreased amplitude of miniature inhibitory currents, reduced evoked inhibitory currents, and reduced synaptic inhibitory potentials.…”
Section: Genetics Of Epilepsy and Autismmentioning
confidence: 99%
“…2). The situation is even more complex as hyperactivation of mTORC1 through removal of TSC1/2 components in mice impairs mGluR-LTD (Auerbach et al 2011;Bateup et al 2011), perhaps through constituitively active S6K-FMRP signaling in these mutant animals. Consistent with this model, rapamycin "rescues" mGluR-LTD in this context of hyperactivated mTORC1 (Auerbach et al 2011).…”
Section: S6 Kinase Targetsmentioning
confidence: 99%